Effect of Sit-at-Home on Business Survival of Foam Manufacturing Firms in Anambra State, Nigeria - Chinwe Mikella Nebolisa (Indonesian Journal of Education and Social Humanities, 2025)
This study examined the effect of sit-at-home on the business survival of foam manufacturing firms in Anambra State, Nigeria. The sit-at-home directive, predominantly observed in Southeast Nigeria, has disrupted economic activities, particularly in the manufacturing sector. The study focused on three core variables movement restriction, fear of violence, and loss of production time, and how they influence business survival. A descriptive survey design was adopted, and data were collected from 150 top-level management staff drawn from 12 foam manufacturing firms across the three senatorial zones of the state. A stratified random sampling technique was used, and data analysis was conducted using linear regression in SPSS. The findings revealed that all three independent variables had significant negative effects on business survival. Movement restriction was found to have a t-value of 10.606, standardized beta (β) = 0.631, and p-value = 0.000, indicating a moderately strong effect. Fear of violence had a t-value of 12.002, β = 0.674, and p = 0.000, suggesting a stronger relationship between security concerns and reduced business sustainability. The most influential factor, loss of production time, recorded a t-value of 13.043, β = 0.702, and p = 0.000, showing that operational downtime has the most critical impact on business survival. The study concludes that sit-at-home orders pose a serious threat to foam manufacturing firms in Anambra State. It recommends enhanced mobility for essential workers, community-based security systems, and flexible production scheduling to mitigate the adverse effects of sit-at-home directives on business survival.